Three dandelion stories - Wurfel, Marlene (My University, 2024)
Three stories that explore the relationship between dandelions and the wisdom of children. The Dandelion Who Couldn't Roar is an original fable by Marlene Wurfel for Tales from the Lilypad. The Legend of the Flower Fairy is based on an Aesop's Fable, rewritten and rearranged by M. Wurfel. The third story about dandelions in the garden is based on a traditional Sufi tale and rewritten and rearranged for TFTL by M. Wurfel. Intro and Outro music by Reid Alexander Whelton. Acoustic music featured Acoustic Guitar by ViraMiller -- https://freesound.org/s/744879/ -- License: Creative Commons 0
Keywords: storytelling; children's stories